2010
DOI: 10.1002/pmic.201000045
|View full text |Cite
|
Sign up to set email alerts
|

Time‐resolved quantitative proteome profiling of host–pathogen interactions: The response of Staphylococcus aureus RN1HG to internalisation by human airway epithelial cells

Abstract: Staphylococcus aureus is a versatile gram-positive pathogen that gains increasing importance due to the rapid spreading of resistances. Functional genomics technologies can provide new insights into the adaptational network of this bacterium and its response to environmental challenges. While functional genomics technologies, including proteomics, have been extensively used to study these phenomena in shake flask cultures, studies of bacteria from in vivo settings lack behind. Particularly for proteomics studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 45 publications
2
41
0
Order By: Relevance
“…In this regard, upregulation of cell wall and techoic acid synthesis genes has been observed in S. aureus following internalization within human lung epithelial cells [35] . Furthermore, in a recent publication reporting the in vivo proteome profile of S. aureus internalized within human bronchial epithelial cells, Schmidt and co-workers [36] showed that, of the 17 potential two-component systems identified in S. aureus , only the response regulator VraR increased in level over time after internalization into host cells. The transcriptional response of S. aureus during intracellular persistence within the mast cell is currently under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, upregulation of cell wall and techoic acid synthesis genes has been observed in S. aureus following internalization within human lung epithelial cells [35] . Furthermore, in a recent publication reporting the in vivo proteome profile of S. aureus internalized within human bronchial epithelial cells, Schmidt and co-workers [36] showed that, of the 17 potential two-component systems identified in S. aureus , only the response regulator VraR increased in level over time after internalization into host cells. The transcriptional response of S. aureus during intracellular persistence within the mast cell is currently under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Proteome analysis of internalized bacteria requires enrichment by differential centrifugation, immunomagnetic separation, or fluorescent assisted cell sorting. A first analysis of the complex proteome adaptation of S. aureus to the intracellular milieu of human epithelial cells was performed in 2010 (Schmidt et al, 2010). Human bronchial epithelial S9 cells were infected with S. aureus HG001 pMV158GFP, which expresses green fluorescent protein constitutively, allowing separation of internalized S. aureus from the whole cell lysate by cell sorting prior to LC-MS/MS analysis of the bacterial proteins (Schmidt et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Combination of peptides and concomitant MS measurement allow the relative quantification of an unlabeled to a labeled sample in one measurement, hence avoiding any variability based on slight day-to-day differences in LC-MS/MS analysis. Despite being usually applied to organisms auxotrophic for arginine/ lysine, the technique has also been used successfully for nematodes (Larance et al, 2011) and bacteria such as Staphylococcus aureus (Schmidt et al, 2010), which, although not being auxotrophic, were opportunistic enough to prefer the supplemented amino acids for peptide biosynthesis. Instead of amino acids, isotopically labeled substrates or nutrients can be applied that lead to a defined relative isotope abundance (RIA) in the biomass.…”
Section: Metabolic Labelingmentioning
confidence: 99%